A Study on Milk Compositions of Hair Goat and Saanen x Hair Goat Crossbreed (F1) under Semi-Intensive Conditions - Orhan Yılmaz; Bahattin Çak; Elvan Ocak; Ahmet Fatih Demirel (Journal of Agricultural Sciences)
This study was carried out to evaluate compositions of milk from Hair goat and Saanen x Hair goat crossbreed (F1) under semi-intensive conditions. The research was conducted on 20 Hair goats and 20 Saanen x Hair goat crossbreed (F1) at Farm for Research and Application of Van Yuzuncu Yil University in Turkey. All the experimental goats were 3 years old and were raised under semi-intensive conditions. In the current study, the average fat, non-fat solid, protein, lactose, total solids, lactic acid, pH values of Hair and crossbreed goat milks were 3.98%, 3.80%; 9.54%, 9.24%; 3.59%, 3.48%; 5.24%, 5.08%; 13.51%, 13.04%; 0.24%, 0.25%; 6.62, 6.64, respectively. Lactation stage had a significant influence (P<0.05; P<0.001) on milk fat, non-fat solid, protein, lactose, total solids contents and lactic acid value in Hair and crossbreed goats' milk. Also, genotype had a significant influence (P<0.001) on non-fat solid, protein, lactose and total solids contents of the milk. In conclusion, Hair goats and crossbreed goats produce milk with a variable milk fat, non-fat solid, protein, lactose, total solids contents at the different stages of lactation. The mean values of milk non-fat solid, protein, lactose and total solids in Hair goats' milk were higher than those of crossbreed goats. Also, milk fat content, lactic acid and pH values in Hair and crossbreed goats' milk were similar.